Jagad batin Ibnu Arabi : menuju manusia dan kewalian paripurna /Abu Abdullah Muhammad bin Ali Bin Muhammad bin Muhammad bin Al-'Arabi Al-Khatimi Al-Tha'i Al-Andalusi dan Mahmud Mahmud Al-Ghurab ; penerjemah, Imam Nawawi ; editor, Taufiq Hakim - ABD ABDULLAH MUHAMMAD BIN ALI BIN MUHAMMAD BIN AL-'ARABI AL-KHATIMI AL-THAÍ AL-ANDALUSI, Abu; Mahmud Mahmud Al-Ghurab; Imam Nawawi; Taufiq Hakim (Indes, 2016)
xiv, 225 hlm. ; 22 cm.